Permanent dentition occlusion in Chinese, Indian and Malay group in Malaysia - Woon Kok-Chin; Thong Yo-Len; Kaiir Rahimah Abdul (Australasian Orthodontic Journal, 1989)
This survey outlines the proportion of the various features of occlusion in the permanent dentition of the three ethnic races, Chinese, Malay and Indian in Malaysia. The mean age of the high school children surveyed was 16.4 years. The Chinese and Malays had almost similar distribution of the different types of occlusion. There was a significantly higher prevalence Clese in occlusion among the Chinese and Malays as compared to the Indians. In addition, an edge to edge mcISor relationship seemed to be a norm m the Chinese (54%) and Malays (50%) whilst the overjet of between 2-4 mm and the overbite of between 1/3 to 2/3 was more normal to Indians (50%). A crowded dentition was also a norm for the three races..